Soybean growth and yield responses at third planting season to residual potassium fertilizer in a vertisol - Henny Kuntyastuti; Runik Dyah Purwaningrahayu; Sri Ayu Dwi Lestari (Brawijaya University, 2019)
Application of fertilizers on previous crops can leave a residue so that it can be used for the next crops. It is necessary to know the extent to which these residues can affect the growth and yield of soybean crops. The objective of this study was to explore the effect of potassium fertilizer residues on growth and yield of soybean crops at third planting season (PS-III) on a vertisol. The research was conducted at dry season using a vertisol from Nganjuk, East Java. The experiment was designed using a factorial randomized block design with two factors and three replications. The first factor was the dose of potassium fertilizer (KCl) in the first planting season (PS-I) of rice, i.e. 0, 500, 1500, and 2000 kg potassium fertilizer/ha. The second factor was the dose of potassium fertilizer in the second planting season (PS-II) of soybean, i.e. 0, 50, 100, 200, and 400 kg potassium fertilizer (KCl)/ha. The soybean variety used was Sinabung. The results showed that fertilizer residues of planting season I and planting season II affected the growth component and yield component of soybean, but did not affect seed yield of soybean. There was no consistent increase on growth component, yield component, or seed yield of soybean with an increasing residual dose of potassium fertilizer of planting season I or planting season II. The residual treatment of 1500 kg potassium/ha at planting season I gave the highest number of branches per plant (2 branches) and seed weight per plant (3.13 g) of soybean. The residual treatment of 50 kg potassium/ha at planting season II gave the highest root nodule weight per plant of 0.10 g and the highest seed weight per plant of 3.33 g.